R.E.N.A.L. Nephrometry Score Profile of Kidney Cancer Patients in Cipto Mangunkusumo Hospital - Rinto Hariwibowo; Agus Rizal AH Hamid; Chaidir Arif Mochtar (National Cancer Center - Dharmais Cancer Hospital, 2019)
Background: The variation of sizes, shapes, and location of kidney cancer complicates the choices of surgical treatment.To determine which technique to use, R.E.N.A.L. nephrometry scoring systems were established. This study was conducted to evaluate R.E.N.A.L.-NS profile in kidney cancer patients at CMHMethod: The data were collected retrospectively from patients that underwent both open and laparoscopic Radical (RN) and Partial Nephrectomy (PN) procedure from 2014-2017. R.E.N.A.L.-NS was calculated based on (R)adius, (E)xophytic/ Endophytic properties, (N)earness to the collecting system, (A)nterior or Posterior position of the tumor, and (L)ocation of the tumor. It was categorized into three complexity: low (4-6 points), medium (7-9 points), and high (10-12 points). Subjects then divided based on the procedure given. Profile of R.E.N.A.L.-NS was shown based on each procedure.Result: In this study, 63 patients were included. 52 underwent RN and 11 underwent PN. In low complexity tumors, all patients received PN. In medium complexity tumors, 22 (78.5%) patients received RN and 6 (21.5%) received PN. All high complexity tumors received RN. Mean renal score in all patient 9.03 (+1.72), RN 9.59 (+1.11), PN 6.36 (+1.6). Higher (R), (N), and (L) scores mean a higher prevalence of RN.Conclusion: Higher complexity tumors were more likely to be treated with RN. Furthermore, (R), (N), and (L) score can be useful to determine RN or PN as a treatment of choice. This study could be used as a reference to another study regarding R.E.N.A.L.-NS in Indonesia.